Pengaruh Pencahayaan dan Pemeliharaan Bangunan Terhadap Kenyamanan Pengunjung (Studi Kasus: Kafe Arabasta Medan) - Suci Lestari; Siti Indah Lestari (Jambura: Jurnal Seni dan Desain, 2022)
In order for a cafe to attract visitors, the cafe needs a comfortable interior and atmosphere. In addition, the concept, layout, lighting and maintenance of the cafe are also important factors that must be considered so that visitors feel comfortable and want to come back. Lighting as a source of lighting can be declared good if the lighting is not too bright and not too dim. It is also necessary to select and adjust to the concept of the building, and the area of the building. A room or building that has insufficient lighting makes visitors feel uncomfortable, a dark place makes the food served not very attractive besides that, the number of mosquitoes is also the cause of the lack of lighting. Every building requires regular maintenance and renovations to keep the building looking comfortable and lively. A building that lacks maintenance makes the building seem shabby and reduces the sense of comfort for visitors. The research method used is descriptive quantitative analysis method, using sampling and measurement methods. In the context of this research in the form of lighting and maintenance at Cafe Arabasta Marelan. The purpose of the study was to find out how lighting and maintenance affect the comfort level of visitors to the Arabasta Marelan cafe.